Электрические и электрооптические свойства пленочных композитов, содержащих органический полимер и гетерополиядерные оксалатные Cu(II)/Mn(II) комплексы - Безнищенко, А.А.; Давиденко, Н.А.; Кокозей, В.Н.; Маханькова, В.Г. (Видавничий дім "Академперіодика" НАН України, 2007)
The features of electric- and photoconductivity as well as the influence of an electric field on the transmission of linearly polarized light in the films of composites based on polyvinylbutyral doped with polymeric particles of the complexes Cu(II)/Mn(II) with ''skeleton'' and ''sandwich'' structures are investigated. The emergent anisotropy of light absorption under the preliminary action of an electrostatic field is observed. The discovered electrooptical properties of the composites are supposed to be caused by changes of the mutual orientation of construction units of the composite under the influence of an external electric field.